Analysis of the content of heavy metals in phytoplankton of the Zaporizhia reservoir - Nikolenko, Yuliia; Fedonenko, Elena (ScienceRise: Biological Science, 2020)
The aim: to investigate the features of the distribution and accumulation of heavy metals by phytoplankton in different parts of the Zaporizhia reservoir. Materials and methods. Phytoplankton samples were collected in the summer of 2019 at 5 sites along the watercourse of the Zaporizhia reservoir. The concentration of heavy metals in the samples was determined using the C115-M1 atomic absorption spectrophotometer, at specific wavelengths corresponding to the maximum absorption of each of the studied metals in accordance with standard methods. The metal content was expressed in mg/kg dry weight. Statistical processing of the obtained data was carried out according to generally accepted methods using the “Microsoft Excel 2010” software. Results. Studies have revealed that the maximum content of Pb, Zn, Cu, Ni, Fe is recorded in the phytoplankton of the creek of the Mokra Sura river; the maximum content of Mn is revealed on the Monastyrsky island, and the content of Cd is the largest in phytoplankton of the lower part of the reservoir. It has been found that the bioconcentration factors of Iron and Magnesium in phytoplankton are characterized as ultrahigh at all the studied points; those of Nickel, Zinc and Copper are characterized as high. Lead and Cadmium bioconcentration factors can be characterized as moderate at most sampling points; however, they are high at the lower part of reservoir. Conclusions. The content of heavy metals in phytoplankton in different parts of the Zaporizhia reservoir differs significantly. Phytoplankton of the Zaporizhia reservoir is able to accumulate heavy metals, especially Iron and Magnesium, which are accumulated in large amounts; the maximum indicators of these elements are recorded in the Samara bay. There is a difference between absolute concentrations of heavy metals in phytoplankton and its accumulative capacity. It is related to both the hydrological and hydrochemical conditions of the area and the qualitative and quantitative composition of phytoplankton